Evaluation of the Cochrane Collaboration’s tool for assessing the risk of bias in randomized trials: focus groups, online survey, proposed recommendations and their implementation - Savović, Jelena; Weeks, Laura; Sterne, Jonathan AC; Turner, Lucy; Altman, Douglas G; Moher, David; Higgins, Julian PT (Systematic reviews, 2014)
Background In 2008, the Cochrane Collaboration introduced a tool for assessing the risk of bias in clinical trials included in Cochrane reviews. The risk of bias (RoB) tool is based on narrative descriptions of evidence-based methodological features known to increase the risk of bias in trials. Methods To assess the usability of this tool, we conducted an evaluation by means of focus groups, online surveys and a face-to-face meeting. We obtained feedback from a range of stakeholders within The Cochrane Collaboration regarding their experiences with, and perceptions of, the RoB tool and associated guidance materials. We then assessed this feedback in a face-to-face meeting of experts and stakeholders and made recommendations for improvements and further developments of the RoB tool. Results The survey attracted 380 responses. Respondents reported taking an average of between 10 and 60 minutes per study to complete their RoB assessments, which 83% deemed acceptable. Most respondents (87% of authors and 95% of editorial staff) thought RoB assessments were an improvement over past approaches to trial quality assessment. Most authors liked the standardized approach (81%) and the ability to provide quotes to support judgements (74%). A third of participants disliked the increased workload and found the wording describing RoB judgements confusing. The RoB domains reported to be the most difficult to assess were incomplete outcome data and selective reporting of outcomes. Authors expressed the need for more guidance on how to incorporate RoB assessments into meta-analyses and review conclusions. Based on this evaluation, recommendations were made for improvements to the RoB tool and the associated guidance. The implementation of these recommendations is currently underway. Conclusions Overall, respondents identified positive experiences and perceptions of the RoB tool. Revisions of the tool and associated guidance made in response to this evaluation, and improved provision of training, may improve implementation.